Bacterial communities, potential pathogens and antibiotic resistance genes of silver-loaded stainless steel pipe wall biofilm in domestic hot water system. (April 2021) - Li, Na; Li, Xing; Shi, Zhi-Yuan; Fan, Xiao-Yan; Zhou, Zhi-Wei
Graphical abstract: Highlights: Ag-SS could inhibit bacteria growth in pipe wall biofilm by contact bacteriostasis. Silver-resistant ( Mesorhizobium ) and -sensitive ( Bradyrhizobium ) genera were found. More than 80 % of unique OTUs were identified as rare taxa in SS and Ag-SS. Legionella, Parachlamydia and Aeromonas were the top 3 silver-sensitive pathogens. Silver led to a slight increase in total abundance but similar distributions of ARGs. Abstract: Silver-loaded stainless steel (Ag-SS) was applied in domestic hot water system (DHWS) to control the biofilm contamination. The antibacterial properties of Ag-SS, as well as the bacterial communities, potential pathogens and antibiotic resistance genes (ARGs) of pipe wall biofilm were investigated, with SS as control. Ag-SS maintained a high antibacterial efficiency on heterotrophic bacteria (70.60 ± 13.22 %) and Escherichia coli (73.56 ± 10.62 %) by contact bacteriostasis. Dominant phyla exhibited a lower relative abundance in Ag-SS than SS. The bacteria were further classified into abundant (≥ 1 %), moderately abundant (0.1∼1 %) and rare (≤ 0.1 %) taxa to investigate their responses to silver. There were 15.33 % of shared operational taxonomic units (OTUs) belonged to abundant taxa, while most unique OTUs (> 80 %) of each sample were identified as rare taxa. As the primary abundant genera, Mesorhizobium and Bradyrhizobium exhibited resistant and sensitive to silver, respectively. Most dominant moderately abundant and rare genera were resistant to silver. Moreover, among 19 detected potential pathogens, Legionella, Parachlamydia and Aeromonas were sensitive to silver, while Pseudomonas and Acinetobacter were resistant to silver. Furthermore, a total of 48 ARGs were detected and they exhibited similar distributions in both samples. The total abundance of ARGs in Ag-SS increased by 0.08 fold compared with that in SS, with efflux pumps as the main resistance mechanisms. This study highlights the different responses of abundant, moderately abundant and rare taxa to silver, and the occurrences of ARGs, confirming that Ag-SS was an effective disinfection strategy for biosafety protection of DHWS.